Prognostic Value of Blood Pressure Variability for Patients With Acute or Subacute Intracerebral Hemorrhage: A Meta-Analysis of Prospective Studies - Liu, Weidong; Zhuang, Xianbo; Zhang, Liyong (Frontiers in Neurology, 2021)
The results on the role of systolic blood pressure (SBP) variability in the functional outcome for patients with intracerebral hemorrhage (ICH) have been inconsistent. Hence, this meta-analysis of prospective studies was conducted to assess the association between SBP variability and poor outcomes in patients with ICH. PubMed, Embase, and the Cochrane Library were electronically searched for eligible studies from their inception to July 2020. The role of SBP variability assessed using standard deviation (SD), coefficient of variation (CV), successive variation (SV), average real variability (ARV), and residual standard deviation (RSD) in the risk of poor functional outcomes was assessed using odds ratio (OR) with 95% confidence interval (CI) through the random-effects model. Seven prospective studies involving 5201 patients with ICH were selected for the final meta-analysis. Increased SBP variability was associated with an increased risk of poor functional outcomes, regardless of its assessment using SD (OR: 1.38; 95% CI: 1.14–1.68; P = 0.001), CV (OR: 1.98; 95% CI: 1.13–3.47; P = 0.017), SV (OR: 1.30; 95% CI: 1.08–1.58; P = 0.006), ARV (OR: 1.13; 95% CI: 1.03–1.24; P = 0.010), or RSD (OR: 1.22; 95% CI: 1.00–1.50; P = 0.049). Moreover, the role of SBP variability in the risk of poor functional outcomes for patients with ICH was affected by country, study design, mean age, stroke type, outcome definition, and study quality. This study indicated that SBP variability was a predictor of poor outcomes for patients with ICH.